THE EFFECT OF PENTACHLOROPHENOL ON THE CHLORELLA HP 01/2B - Lê Thị Anh Tú; Lâm Ngọc Tuấn (Tạp chí Khoa học Đại học Đà Lạt)
The Pentachlorophenol (PCP) tolerance of Chlorella HP 01 / 2B was studied. Chlorella HP 01/ 2B not only had the ability to survive in an environment having PCP, but also showed some tolerance to other chlorophenols including 2-chlorophenol (CP), 2.4-Dichlorophenol (DCP), 2,4,6-trichlorophenol (TCP). PCP inhibited the growth of the algae initial growth. After the resumed growth, photosynthetic and growth rate of microalgae were comparable with that of the control. The effect of PCP on algae depended on the initial density of algae Chlorella HP 01/2B and time when adding PCP after inoculation.